‘I actually felt like I was a researcher myself.’ On involving children in the analysis of qualitative paediatric research in the Netherlands - Malou L Luchtenberg; Els L M Maeckelberghe; AA Eduard Verhagen (BMJ Open)
Objectives To evaluate the feasibility of a new approach to paediatric research whereby we involved children in analysing qualitative data, and to reflect on the involvement process.Setting This was a single-centre, qualitative study in the Netherlands. It consisted of research meetings with individual children at home (Phase I) or group meetings at school (Phase II). In Phase I, we identified themes from a video interview during five one-on-one meetings between a child co-researcher and the adult researcher. In Phase II, during two group meetings, we explored the themes in detail using fragments from 16 interviews.Participants We involved 14 school children (aged 10 to 14 years) as co-researchers to analyse children’s interviews about their experience while participating in medical research. Notes were taken, and children provided feedback. A thematic analysis was performed using a framework approach.Results All co-researchers identified themes. The time needed to complete the task varied, as did the extent to which the meetings needed to be structured to improve concentration. The children rated time investment as adequate and they considered acting as co-researcher interesting and fun, adding that they had learnt new skills and gained new knowledge. The experience also led them to reflect on health matters in their own lives. The adult researchers considered the process relatively time intensive, but the project did result in a more critical assessment of their own work.Conclusion The new, two-phase approach of involving children to help analyse qualitative data is a feasible research method. The novelty lies in involving children to help identify themes from original interview data, thereby limiting preselection of data by adults, before exploring these themes in detail. Videos make it easier for children to understand the data and to empathise with the interviewees, and limits time investment.